Effect of Sintering Additives on Relative Density and Li‐ion Conductivity of Nb‐Doped Li7La3ZrO12 Solid Electrolyte. Issue 1 (11th October 2016) - Rosero‐Navarro, Nataly Carolina; Yamashita, Taira; Miura, Akira; Higuchi, Mikio; Tadanaga, Kiyoharu
Abstract : Lithium ion conductors with garnet‐type structure are promising candidates for applications in all solid‐state lithium ion batteries, because these materials present a high chemical stability against Li metal and a rather high Li + conductivity (10 −3 –10 −4 S/cm). Producing densified Li‐ion conductors by lowering sintering temperature is an important issue, which can achieve high Li conductivity in garnet oxide by preventing the evaporation of lithium and a good Li‐ion conduction in grain boundary between garnet oxides. In this study, we concentrate on the use of sintering additives to enhance densification and microstructure of Li7 La3 ZrNbO12 at sintering temperature of 900°C. Glasses in the LiO2 ‐B2 O3 ‐SiO2 ‐CaO‐Al2 O3 (LBSCA) and BaO‐B2 O3 ‐SiO2 ‐CaO‐Al2 O3 (BBSCA) system with low softening temperature (<700°C) were used to modify the grain‐boundary resistance during sintering process. Lithium compounds with low melting point (<850°C) such as LiF, Li2 CO3, and LiOH were also studied to improve the rearrangement of grains during the initial and middle stages of sintering. Among these sintering additives, LBSCA and BBSCA were proved to be better sintering additives at reducing the porosity of the pellets and improving connectivity between the grains. Glass additives produced relative densities of 85–92%, whereas those of lithium compounds were 62–77%. Li7 La3 ZrNbO12 sintered with 4 wt% of LBSCA at 900°C for 10 h achieved a rather high relative density of 85% and total Li‐ion conductivity of 0.8 × 10 −4 S/cm at room temperature (30°C).